2018
DOI: 10.5811/cpcem.2018.2.37291
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy in the Emergency Department: A FOCUS Heart Breaker

Abstract: Takotsubo cardiomyopathy (TCM) is an important condition for the emergency physician to consider in patients with cardiovascular symptoms. A 70-year-old woman presented with chest pain and nausea following emotional trauma. She had an elevated troponin and a normal electrocardiogram with no history of previous cardiac disease. Point-of-care focused cardiac ultrasound (FOCUS) showed reduced left ventricular systolic function with mid to apical hypokinesis. Cardiac catheterization revealed clean coronary arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…9 However, bedside echocardiography has previously been reported to have a role in suggesting TS in the ED. [10][11][12] Our three-case series further confirms that the circumferential apical ballooning of TS can be identified in the ED with POCUS performed by emergency physicians. Further, we show how early recognition may influence the patient's clinical course.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…9 However, bedside echocardiography has previously been reported to have a role in suggesting TS in the ED. [10][11][12] Our three-case series further confirms that the circumferential apical ballooning of TS can be identified in the ED with POCUS performed by emergency physicians. Further, we show how early recognition may influence the patient's clinical course.…”
Section: Introductionsupporting
confidence: 77%
“…As stated, current algorithms do not explicitly include emergency POCUS as part of the diagnostic pathway 9 . However, bedside echocardiography has previously been reported to have a role in suggesting TS in the ED 10‐12 . Our three‐case series further confirms that the circumferential apical ballooning of TS can be identified in the ED with POCUS performed by emergency physicians.…”
Section: Introductionsupporting
confidence: 74%
“…Takotsubo cardiomyopathy has often been associated with hypercatecholaminergic states. A recent study showed that patients with TTC had catecholamine levels that were 2 to 3 times greater than patients with classic MI's, resulting in microvascular spasm and myocardial stunning likely secondary to beta-receptor mediated sympathetic stimuli [3,12-14]. Regarding the role of marijuana in TTC, it has been theorized that the endocannabinoid system may also cause physiologic stress as illustrated above, leading to cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although TCM is a diagnosis of exclusion, POCUS has been described as a modality that may help identify these patients and affect downstream decision‐making. 3 , 4 There is no clear suggested management for patients with TCM, and care is supportive. Most patients recover over the course of weeks to months.…”
Section: Diagnosis and Teaching Pointsmentioning
confidence: 99%